ETHNOBOTANICAL STUDY OF WILD PLANTS OF PARSA DISTRICT, NEPAL - Singh, Shila (Ecoprint: An International Journal of Ecology, 2017)
The present study was carried out to assess ethnobotanical information of some wild plants used by the Tharu community of Parsa district of Nepal. The study was conducted in four villages; Gadi, Madhuban mathwal, Sonbarsa and Shanker Sharaiya. The study focuses on the ethno botanical practices of the Tharu community and documentation of the traditional knowledge for the benefit of mankind. The information presented in this paper was gathered by frequent field visits in the villages, participatory observations, group discussion, interviews with local knowledgeable people in the year 2013 from February to November. A total of 46 ethnomedicinal wild plant species belonging to 31 families and 44 genera are documented in this study. Some new ethno medicinal uses of the plant species like Ficus benghalensis, Gymnema sylvestre, Mimosa pudica Oroxylem indicum, Hibiscus-rosa sinensis, Hydragia anomala, Matricaria chammomilla, Kalanchoe spathelata, Leucas cephalotes, Madhuca indica, Murraya koenigii, Melia azedarachta, Mentha arvensis, Nephrolepsis cordifolia, Morus alba, Nyctanthes arbortritris, Ocimum sanctum, Oxalis corniculata, Phyllanthus amarus, Plumbago zeylanica, Pterocarplus marsupium, Putranjiva roxburghii and Rauvolfia serpentine among Tharu community of Parsa district of Nepal are discussed in the present study. ECOPRINT 24: 1-12, 2017